Risk factors associated with indoor transmission during home quarantine of COVID-19 patients - Liu, Yang; Chai, Yan-Hua; Wu, Yi-Fan; Zhang, Yu-Wei; Wang, Ling; Yang, Ling; Shi, Yi-Han; Wang, Le-Le; Zhang, Li-Sha; Chen, Yan; Fan, Rui; Wen, Yu-Hua; et al. (Frontiers in Public Health, 2023)
Purpose: The study aimed to identify potential risk factors for family transmission and to provide precautionary guidelines for the general public during novel Coronavirus disease 2019 (COVID-19) waves. Methods: A retrospective cohort study with numerous COVID-19 patients recruited was conducted in Shanghai. Epidemiological data including transmission details, demographics, vaccination status, symptoms, comorbidities, antigen test, living environment, residential ventilation, disinfection and medical treatment of each participant were collected and risk factors for family transmission were determined. Results: A total of 2334 COVID-19 patients participated. Compared with non-cohabitation infected patients, cohabitated ones were younger (p=0.019), more commonly unvaccinated (p=0.048) or exposed to infections (p<0.001), and had higher rates of symptoms (p=0.003) or shared living room (p<0.001). Risk factors analysis showed that the 2019-nCov antigen positive (OR=1.86, 95%CI 1.40-2.48, p<0.001), symptoms development (OR=1.86, 95%CI 1.34-2.58, p<0.001), direct contact exposure (OR=1.47, 95%CI 1.09-1.96, p=0.010) were independent risk factors for the cohabitant transmission of COVID-19, and a separate room with a separate toilet could reduce the risk of family transmission (OR=0.62, 95%CI 0.41-0.92, p=0.018). Conclusion: Patients showing negative 2019-nCov antigen tests, being asymptomatic, living in a separate room with a separate toilet, or actively avoiding direct contact with cohabitants were at low risk of family transmission, and the study recommended that avoiding direct contact and residential disinfection could reduce the risk of all cohabitants within the same house being infected with COVID-19.